Potential Barrier of (Zn,Nb)SnO2-Films Induced by Microwave Thermal Diffusion of Cr3+ for Low-Voltage Varistor - Lustosa, Glauco M. M. M. [UNESP]; Da Costa, João Paulo De Campos; Perazolli, Leinig A. [UNESP]; Stojanovic, Biljana D.; Zaghete, Maria Aparecida [UNESP] (Wiley, 2016)
The effect of Cr3+ on the electrical properties of SnO2-based films deposited by electrophoresis on Si/Pt substrate was considered. The films were sintered in a microwave oven at 1000C/40 min and then the surface was modified with deposition of Cr3+ ions by electrophoresis. The diffusion of Cr3+ contributes to the modification of the potential barrier formed on the grain boundary improving the electrical properties due to electron acceptor species adsorption on the grain boundary. The influence on the properties of grain boundary was verified by I versus V characterization in as a function of temperature. The films showed nonlinear coefficient over 9, potential barrier height over 0.5 eV and resistivity greater than 107 Ω·cm. 4 samples were prepared at same conditions and presented similar electrical behavior, showing the efficiency of technique on reproducibility to varistor properties control. Thereby the nonlinear coefficient increases while decreasing the conductivity of the system is noticed.